Macroeconomic Consequences of Trump Era Protectionist Policies on Global Trade and Business Stability - Achmad Daengs (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The swift integration of cryptocurrencies into mainstream financial s ystems has attracted a growing number of new investors to conventional markets. This segment entering digital asset environments for the initial time is distinctly exposed to inherent dangers like unpredictable price fluctuations, uncertainty in regulations, security threats and limited protections for members. This investigation aims to study how perceptions of monetary peril influence the investment choices of these fledgling contributors. By utilizing a quantitative, cross-sectional, correlational design, the research gathered primary data from 300 initial cryptocurrency buyers through an online structured questionnaire. The data was analyzed using descriptive statistics, factor analysis, correlation, multiple direct regression and moderation analysis. Key results indicate that heightened perceptions of fiscal risk,particularly regarding capital depletion and unstable markets,are significantly associated with cautious investment behaviors for example preferring long-term possession of assets and avoiding leverage. Additionally, the work found demographic variables such as age and income moderate the strength of these links. Grounded in the Conservation of Resources theory, the analysis offers a psychological explanation for the resource-preserving strategies embraced by new crypto investors. By focusing on an understudied population within the behavioral finance domain, this examination contributes to theoretical understanding of financial decision-making under ambiguity and furnishes practical insights for fintech platforms, investor education programs and regulatory frameworks aimed at enhancing the security and inclusiveness of digital monetary markets.